Musashino Art University Museum & Library, Tokyo Sou Fujimoto. - Pollock, Naomi R. (Architectural Record, 2011)
The article reviews the architectural design of the Musashino Art University Museum & Library in Tokyo, Japan, designed by architecture firm Sou Fujimoto Architects.